Differentiation of Body Fat Composition Measurement Between Skinfold Caliper and Bioelectrical Impedance analysis Methods Among Athletes (Jurnal kesehatan komunitas (Journal of community health), 2021)
Research about Skinfold Caliper (SKF) and Bioelectrical Impedance Analysis (BIA) has been frequently studied in athletes. Accurate of SKF is dependent on the technique, skill, and experience of the tester, whereas BIA is less time consuming and easily administered by investigators. The study aimed was to analyze the mean difference of body fat composition (BF%) between SKF and BIA methods among bodybuilders, heavy lifter, and weight lifter athletes. This was an observational analytic research with a cross-sectional design. The data were obtained from direct measurements to 30 athletes (21 men and 9 women). The percentage of body fat data were obtained by SKF and BIA and also anthropometric data (weight and height). The mean of BF percentages was analyzed by multiple paired t-test. The study showed a significant difference in BF% between SKF and BIA methods according to gender, sport, and Body Mass Index (BMI) categories (p